Rancang Bangun Aplikasi Pengelolaan Data Statistik Sosial Berbasis Web menggunakan Metode Kanban - Odista Dwi Putra; Ulfa Khaira; Rizqa Raaiqa Bintana (Jurnal Publikasi Teknik Informatika, 2026)
Statistical data is a crucial foundation for evidence-based government policymaking and public accountability. The Social Statistics Division of Badan Pusat Statistik (BPS) Jambi Province currently manages its data through fragmented Microsoft Excel files, causing inefficiencies such as difficulty locating tables, vulnerability to manual entry errors, and the absence of a structured verification pathway before data reaches external users. This study designed and developed SISTADISS (Sistem Pengelolaan Data Statistik Sosial), a web-based application for social statistics data management, using the Kanban agile development method. The system was built using Next.js, Neon PostgreSQL, Prisma ORM, and Tailwind CSS. Authentication is implemented through an SSO integration for internal BPS staff and a bcryptjs-JWT mechanism for external users. Development was conducted across four iterative cycles: user authentication, dynamic statistical table display, data management via a change-request workflow, and a multi-level verification module. All nineteen functional requirements were validated through black-box testing, yielding a 100% pass rate across three user roles: Admin Verifikasi, Petugas, and Pengguna. The system was deployed on Vercel and is accessible at the BPS Jambi Province institutional domain.